Job practice: An evaluation and a comparison with vocational labour market training programmes - Anders Forslund; Linus Liljeberg; Leah von Trott zu Solz (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
We have estimated effects of job practice for participants entering the programme between 1999 and 2006. On average the programme had a moderately sized positive effect for the participants - the expected time to work for the unemployed participants was reduced by around six per cent over a 700 days long follow-up horizon counted from the programme start date. Participation also gave rise to higher future labour income and a reduction in social assistance take-up. When we compare job practice with labour market training, we get the somewhat paradoxical result that job practice participants would have gained more from training, while the training participants would have gained equally much from both programmes. A re-shuffling of participants between the programmes, hence, would have been associated with higher average effects.
Keywords: D04; J08; J18; J64; 330; labour market policies; evaluation; Berufliche Integration; Arbeitsmarktpolitik; Wirkungsanalyse; Schweden